KUALITAS MIKROBIOLOGI ES BATU KRISTAL DAN HYGIENE SANITASI SEPANJANG RANTAI DISTRIBUSI DI SURABAYA - Nur Zumairotul Muna; AT. Diana Nerawati; Rachmaniyah . (GEMA LINGKUNGAN KESEHATAN, 2016)
Crystal ice cube consumed by people is distributed through distribution chain from factories, agents, and ice traders in Surabaya. Each distribution chain posses risk of contamination to the quality of the ice, one of which is microbiological contamination that cause health problems to consumers. This is descriptive study aimed to obtain microbiological quality of crystal ice cube and hygiene sanitation throughout distribution chain in Surabaya. Sampling and observations were conducted sequentially in the same day, in different time and with 3 time repetition for 3 days in a row. Data were analyzed descriptively. The result showed  that the ice crystals did not contain E. coli yet contained MPN Coliform. The rate of MPN Coliform on ice at factory  was 10 colonies / 100 cc sample, at agent was 12-15 colonies / 100 cc sample, and at merchant were 15-43 colonies / 100 cc sample. Hygiene sanitation affecting MPN Coliform in crystal ice are non standard raw materials, production process, transportation, and the handlers. In conclusion, microbiological quality of crystal ice cube along the distribution chain in Surabaya with E. coli parameter did not meet standard. Health Department needs to conduct surveillance on a regular basis. Factory of ice cube needs to  make Standard Operating Procedures. Agents  and traders need to improve hygiene sanitation of conveyance, transport personnel, equipment, and handlers.  Keywords : Ice Cube Crystals, Chain Distribution, Hygiene Sanitation, MPN Coliform, E. coli